Different control applications on a vehicle using fuzzy logic control - Yagiz, Nurkan; Sakman, L. Emir; Guclu, Rahmi (SPRINGER INDIA, 2008)
In this paper, the active suspension control of a vehicle model that has five degrees of freedom with a passenger seat using a fuzzy logic controller is studied. Three cases are taken into account as different control applications. In the first case, the vehicle model having passive suspensions with an active passenger seat is controlled. In the second case, active suspensions with passive passenger seat combination are controlled. In the third case, both the passenger seat and suspensions have active controllers. Vibrations of the passenger seat in the three cases due to road bump input are simulated. At the end of the study, the results are compared in order to select the combination that supplies the best ride comfort.
Keywords: vehicle vibrations; active suspensions; fuzzy logic control; vehicle model; ACTIVE SUSPENSION; Engineering